2022
DOI: 10.3390/children9060832
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue on Ischemic Stroke in Children

Abstract: The occurrence of arterial ischemic stroke (AIS) is a serious medical problem due to the deleterious neurological consequences that affect the daily functioning of the patient as well as the costs of medical care and rehabilitation [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Multifactorial background of stroke occurrence in children is different from adults. Genetic risk factors have more clinical relevance, compared with non-genetic risk factors—environmental factors in children [ 10 , 11 ]. In order to address this important global public health concern, continued efforts on screening the trend of stroke diseases burden and its modifiable risk factors, studying cutting-edge clinical assessment methods and techniques with higher sensitivity and specificity, and developing education programs of diagnosis and management in multidisciplinary medical personnel including cardiologists, hematologists, and cardiac intensivists, etc., were critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifactorial background of stroke occurrence in children is different from adults. Genetic risk factors have more clinical relevance, compared with non-genetic risk factors—environmental factors in children [ 10 , 11 ]. In order to address this important global public health concern, continued efforts on screening the trend of stroke diseases burden and its modifiable risk factors, studying cutting-edge clinical assessment methods and techniques with higher sensitivity and specificity, and developing education programs of diagnosis and management in multidisciplinary medical personnel including cardiologists, hematologists, and cardiac intensivists, etc., were critical.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that central nervous system infections, vitamin K deficiency-related bleeding disorder, inherited coagulation disorders, and arteriovenous malformations were the most common risk factors for childhood stroke [ 4 , 7 9 ]. Compare with genetic risk factors, non-genetic risk factors, such as environmental factors (which are common in adults) seem to have low or no clinical relevance in children [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%